DENDA ADAT TERHADAP PERJANJIAN PEMBATALAN PERTUNANGAN DI KABUPATEN PELALAWAN - Martha, Cici Wia; Firdaus, Firdaus; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The engagement process usually has a tradition of giving each other gifts.This engagement is still possible to be canceled. Unilaterally canceling anengagement, among other things, provides reasonable (reasonable) reasons forthe other party to cancel the marriage or resign without mentioning the reasonsthat can be recognized. In practice, the cancellation of the engagement of one ofthe parties does not fulfill its promise, then the sign must be returned in theamount or multiplied from what was received but the fine is replaced not inaccordance with customary provisions causing conflicts. The purpose of writingthis thesis, namely: First To find out the mechanism of fines for the cancellation ofthe engagement agreement, Second To find out efforts to resolve disputes on thefulfillment of fines of the cancellation agreement by women who are not inaccordance with customary provisions.This type of research can be classified as sociological, because in this studythe authors directly conducted research at the location or place under study inorder to provide a complete and clear picture of the problem under study. Thisresearch was conducted in Angkasa Village, Bandar Petalangan Subdistrict,Pelalawan Regency, while the population and sample were all parties related tothe problems examined in this study, the source of the data used were primarydata, secondary data and tertiary data, data collection techniques in this studywith interviews and literature study.From the results of the study, it can be concluded that the first 2 things, themechanism of the fine for the engagement cancellation agreement has beenrunning properly where the woman replaces the fine with a plot of land on top ofthe house. can be valued with money according to customary provisions as muchas 2 (two) times. Secondly, efforts to resolve disputes regarding the fulfillment offines for cancellation of engagement by women that are not in accordance withadat provisions have already led to deliberations led by customary stakeholdersthemselves. However, the results of the deliberation were not valued and were notaccepted by either party. So ninik mamak provides a solution to resolve thisproblem to the legal path of the court where the decision will be incraht (legallybinding) and binding on the parties.Keywords: Customary Penalty-Cancellation-Engagement.